Voluntary Adoption of Corporate Governance Mechanisms - Anita Anand; Frank Milne; Lynnette Purda (Queen's University, Department of Economics, 2006)
We model firms' incentives to voluntarily adopt corporate governance mechanisms and hypothesize that management's ability to extract private benefits, the need for external funds, and the ease with which a firm's assets may be monitored are important determinants of the level of governance. Using hand-collected data, we test these hypotheses and examine firms' propensity to adopt recommended but not required governance standards from their home and neighboring country's jurisdictions. We document that a significant level of voluntary adoption occurs and that this level has been both increasing over time and declining in variability across firms. Governance mechanisms are least likely to be voluntarily implemented when management controls a significant portion of common stock votes or a majority owner exists. In contrast, voluntary adoption increases when the firm faces significant investment opportunities and employs large levels of expenditures which are difficult to monitor such as research and development expenses.
Keywords: G34; 330; Corporate Governance; Empirial Finance